Process of Communication Based on Buddhism for Developing of Public Relation at Rajabhat Maha Sarakham University - สีเสน, บญุคง; วรธมฺโม, พระวรเวช; ยตฺุติธโร, พระกิตติ (Journal for Developing the Social and Community, 2016)
This research aimed to (2) study a theoretical concept of the public relations, (3) a process of the public relations based on Buddhism at the Rajabhatmahasarakham University, and (4) to get Buddhist information applied to the public relations of the Rajabhatmahasarakham University. In this research, there was the analysis of the Buddhist data through a theory of the Public relations in the West and Thailand. A research used questionnaire and interviewed the target groups, i.e. personnel of the Rajabhatmahasarakham University: administrators, lecturers, officers and students. The data analysis was done in the computer's program. The result of this research was found that; Model and a process of the Buddhistbased communication were right and proper to develop the public relations at Rajabhatmahasarakham University. Generally, the public relations at this university requited many types of a modern communication tool such as radio, television, cable TV, internet, and magazine. A personal media in the communication system was the achievement media. It was most important because it covered representation of feelings, thoughts, and speech through the communication tools for more understanding among people. In this person media, the use of speech in the communication system at the university was still problematic. However, if Sammavaca in Buddhism was applied to the public relations, it caused harmony among people, effective public relations and good image. Generally, Sammavaca (Right Speech) consisted of 5 components: (1) true speech, (2) polite speech, (3) useful speech, (4) kind speech and (5) speech in a proper time. All of these components could make more achievement of the communication management. Moreover, a researcher found that the components of communication: a sender, a receiver, a channel of receiving a message and a message through theories in the West would be complete if there was the applied Buddhist principles to the public relations. It will be operating of institute as with smooth made for the ideal of the university as a community where everyone proud.